One-stage reconstruction of isolated and combined tendon defects with the vascularized adductor magnus tendon graft: Surgical technique and preliminary results. Issue 7 (July 2016) - Neuwirth, M.; Bürger, H.; Palle, W.; Rab, M.
Summary: Introduction: Secondary reconstructions of isolated and combined tendon defects are still a challenge for plastic surgeons. Due to its reliable anatomy, reconstructive potential and low donor-site morbidity, the medial femoral condyle is an ideal area for harvesting isolated and combined tendon flaps. This study evaluates our preliminary results with the vascularized adductor magnus tendon flap. Patient and methods: The study included six patients who received a vascularized tendon flap (upper extremity: three patients; lower extremity: three patients) from 2011 to 2015. For three patients, the adductor magnus tendon was used as a single flap; for the other three patients, the tendon was included in a composite flap. A retrospective chart review provided the patients' demographic data, surgical details and the post-operative course. The further objective and patient-reported outcome was evaluated with a long-term follow-up. Results: All of the free vascularized flaps healed without complications and with good vascularization upon duplex ultrasonography. One patient did, however, require revision surgery in the late post-operative course. At the end point, all patients showed good functional results without any donor-site morbidity. Conclusion: For carefully selected isolated and combined tendon defects on the upper and lower extremities, the vascularized adductor magnus tendon flap provides a reliable and versatile method for microsurgical reconstruction.